Preparation of rice bran protein isolates using three-phase partitioning and its properties - Phongthai, Suphat; Rawdkuen, Saroat (Food and Applied Bioscience Journal, 2017)
Rice bran is an economical source of natural plant-based protein. Nowadays, there are many inventions for trying to extract rice bran protein. However, the methods for recovering protein from the extract usually provide low yield. So, the application of three-phase partitioning (TPP) was studied. To recover the proteins from crude rice bran extract, TPP condition including the ratio of t-butanol to crude rice bran extract and the concentration of ammonium sulfate was optimized. The optimal condition achieving the highest rice bran protein isolates (RBPI) recovery (98.59±3.52%) was the ratio of t-butanol to crude rice bran extract of 2.0:1.0 with 40% of ammonium sulfate. Molecular weight (MW) of rice bran protein hydrolysates (RBPH) obtained by using crude enzyme from papaya latex (activity=8,658.67±44.06 Unit/mL) ranged between <7.51 to 31.83 kDa. The total phenolic content (TPC) of RBPI and RBPH was 244.93±5.01 and 367.40±4.68 μg Gallic acid/mL, respectively. Moreover, these rice bran proteins also showed antioxidants activity in terms of radical scavenging activity (17.84±0.45 to 44.51±0.44%) and ferric reducing activity (584.67±2.65 to 924.33±6.11 μmoL FeSO4/L). According the results, TPP could be used as an alternative method to recover protein with a high yield and bioavailability properties.